Toward a Taxonomy of Uncanny Objects: A Phenomenological Approach - Ryba, Thomas (The Development of Eco-Phenomenology as An Interpretative Paradigm of The Living World, 2022)
This chapter proposes a Husserlian phenomenological approach to the uncanny, to make some first steps toward a taxonomy of uncanny objects. Making use of the insights of Husserl, Steinbock and Tymieniecka, it proceeds according to the principle that description ought to precede theory. Thus, against a premature theoretical explanation of uncanniness, it concentrates on some objective characteristics of objects that contribute to the experience of the uncanny, arguing that the notions of home-world, alien-world, internal and external noematic horizons of objects are useful in explicating what makes an uncanny object "uncanny". Broader in scope than some other treatments, this chapter includes discussion not only of phenomena that may be classified as negatively uncanny but also phenomena that are positively and neutrally uncanny. The result is a nine-part taxonomy which is applied in the interpretation of representative (but variegated) examples of complex uncanny objects.